Assessing the efficacy of pictorial preference assessments for children with developmental disabilities. Issue 4 (16th August 2016) - Heinicke, Megan R.; Carr, James E.; Pence, Sacha T.; Zias, Danika R.; Valentino, Amber L.; Falligant, John M.
Abstract : Past research has demonstrated that pictorial preference assessments can predict subsequent reinforcement effects for individuals with developmental disabilities only when access to the selected stimulus is provided contingent on a pictorial selection. The purpose of the present investigation was to assess more comprehensively the feasibility of the pictorial format with children with developmental disabilities. In Experiment 1, prerequisite skill assessments were conducted, and the role of a contingent reinforcer was assessed by comparing the results from the pictorial assessment without contingent access to a reinforcer assessment. If contingent access was found to be necessary, the effects of schedule thinning were evaluated to determine whether a pictorial format could be made more practical in Experiment 2. The pictorial format without contingent access was successful with only some participants. However, schedule thinning was found to be an effective method to establish conditioned reinforcement properties for pictorial stimuli to create a more practical assessment for a subset of participants.